MOAMBONGI RONGA MONGGOLUPE: Conflict and Integration in The Tolaki People of Konawe - Koodoh, Erens Elvianus (Journal of Islam and Science, 2016)
This study aims to identify the various socio-cultural conditions of Tolaki people in Konawe that often resulting of inter-families conflict. The process of identifying socio-cultural conditions are then directed to see the correlation between socio-cultural conditions with the types of inter-families conflict and how inter-families conflicts was resolved at the community level. In addition, this study also aimed to determine and analyze the types of inter-families conflicts that exist in the Tolaki and processes for conflict resolution among families in the Tolaki in Konawe. Perspective theory used in order to analyze the data is a conflicts perspective and family conflicts, structural functional perspective, and conflict resolution. Conflicts Perspective and family conflicts is to reveal the types of inter-families conflicts that often occurred in Tolaki people. Structural functional perspective is essentially an effort to show the functional relation between a cultural element or a socio-cultural phenomenon particular to the social structure that exists in a society. While the perspective of conflict resolution is to reveal the strategies used by the Tolaki people in the process of conflict resolution. Observation and interview is the method used in this study in order to find the data. While the research informants are divided into two categories, the key informant were traditional leaders and ordinary informants that public figures such as religious leaders, government within the scope of sub-district, village, and community members both at the level of individuals, families, and communities. Selection of traditional leaders, religious leaders, and government within the scope of sub-district and village as an informant because they are involved in conflict resolution While the selection of members of the public of the level of individuals, families, and society are because they have or are involved in a conflict. The results of this study indicate that the conflict in the Tolaki conflicts took the form of closed and open conflict. While the source or cause of the conflict is tulura (speech), peowai (actions), and powaihako (behavior). The sources of this conflict then manifested in the daily life of Tolaki people become sisala'a ine perapua (conflict in marriage), sisala'a ine Hapo- Hapo (conflict by treasure), and conflict in social relations. Social and cultural conditions that often lead to inter-families conflicts is the difference in social strata, economic inequality, and religious differences. Tolaki People then settle their conflict through the completion of melanggahako, mesokei, peohala, mombopoo'rai, sombalabu, and mosehe.